An Approach to the Biblical Context of the Fertile Crescent: Importance and resignifications in the Contemporary World - Duperré, Gustavo Norberto (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2019)
The impetus towards the contextualization of the facts referred to in the Old and New Testament is made evident in the spread of its contents and its translation into more languages than any other book in History. From the legendary Ur, Sinai and Ancient Egypt to name some of the territories, the echoes of a complex historical process have reached our days, which in the last centuries have increased the religious political controversies in the globe. Still, the Bible as a historical account together with the archaeological findings have become the argumentative basis of significance to the forms of visual representation in the history of art. Their level of substantiation have brought up the debate with respect to the reconstruction of the biblical events, and has indirectly allowed us to get to know the Judaeo-Christian world through the symbolic expressive typologies in each culture.